Construction and Validation of Coronary CTA Health Education Program Based on Knowledge to Action Framework Combined with Teach-Back Method - Xu Y; Ma L; Jin L; Xu L; Gu Y; You J (Nursing: Research and Reviews)
Yuhong Xu, Lili Ma, Liqing Jin, Liuyan Xu, Yan Gu, Jia You East Hospital Affiliated to Tongji University, Tongji University Medical College, Shanghai East Hospital, Shanghai, 200123, People’s Republic of ChinaCorrespondence: Lili Ma, East Hospital Affiliated to Tongji University, Shanghai East Hospital, Shanghai, 200120, People’s Republic of China, Tel +86-1391823391, Email 719595961@qq.com, 19916567126@163.comIntroduction: The success of coronary CT angiography (CCTA) depends not only on the scan sequence parameters, but also on adequate preparation and active cooperation. At present, there are many reports about CCTA nursing and education, but there is no systematic and complete CCTA health education program.Aim: Construct CCTA health education program and verify its effect.Methods: Through literature research, evidence extraction and expert consultation, the CCTA health education program was constructed. 298 patients who underwent CCTA examination in the imaging department of our hospital were selected and randomly divided into the control group (148 cases) and the intervention group (150 cases) who were given the health education program based on KTA combined with feedback method. The effect was verified by comparing the CCTA knowledge self perception score, state anxiety score and examination duration between the two groups.Results: 1. The CCTA health education program based on KTA joint feedback method is constructed. 2. The scheme shows significant differences in seven aspects such as CCTA knowledge self perception score.Conclusion: The CCTA health education program constructed in this study can improve patients’ self-awareness of CCTA knowledge and the success rate of one-time examination, increase satisfaction, ensure image quality, reduce patients’ anxiety and tension, stabilize heart rate and heart rate, shorten examination time, and improve work efficiency.Keywords: coronary artery, feedback method, health education, knowledge transformation theory, multi-slice spiral CT, nursing